2003
DOI: 10.1562/0031-8655(2003)077<0186:peoasp>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Effects of Antioxidant Substituted Porphyrin Photosensitizers on Gram-positive and -negative Bacteria¶

Abstract: Photodynamic treatment of the gram-negative bacteria Escherichia coli B and Acinetobacter baumannii and the gram-positive bacterium Staphylococcus aureus was performed using two newly devised and synthesized antioxidant carrier photosensitizers (antioxidant carrier sensitizers-2 [ACS-2] and antioxidant carrier sensitizers-3 [ACS-3]), which are butyl hydroxy toluene and propyl gallate substituted haematoporphyrins, respectively. It was found that ACS-2 is less reactive than other photosensitizers previously use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…Several research groups have reported results on the PDT enhancing activities of certain antioxidant molecules, such as ascorbate,104 3(2)-tetra-butyl-4-hydroxyanisole,105 epigallocatechin-3-gallate,106 α-tocopherol,107 and trolox ([±]-6-hydroxyl-2, 5, 7, 8-tetramethyl chromane-2-carboxylic acid, a water soluble vitamin E analogue) 108. Based on these intriguing results, some antioxidant carrier sensitizers (ACSs) which conjugated PSs and antioxidants together were designed and studied for their photodynamic anticancer109 and antibacterial activities 110. It was noted that the PDT effect of such ACSs is based on the so called type III (or MTO) mechanism which increases the singlet oxygen production via inhibition of the interaction between triplet excited PS and native free radicals 109…”
Section: Pdtmentioning
confidence: 99%
“…Several research groups have reported results on the PDT enhancing activities of certain antioxidant molecules, such as ascorbate,104 3(2)-tetra-butyl-4-hydroxyanisole,105 epigallocatechin-3-gallate,106 α-tocopherol,107 and trolox ([±]-6-hydroxyl-2, 5, 7, 8-tetramethyl chromane-2-carboxylic acid, a water soluble vitamin E analogue) 108. Based on these intriguing results, some antioxidant carrier sensitizers (ACSs) which conjugated PSs and antioxidants together were designed and studied for their photodynamic anticancer109 and antibacterial activities 110. It was noted that the PDT effect of such ACSs is based on the so called type III (or MTO) mechanism which increases the singlet oxygen production via inhibition of the interaction between triplet excited PS and native free radicals 109…”
Section: Pdtmentioning
confidence: 99%
“…Porphyrins can be transformed into cationic entities through the insertion of positively charged substituents in the peripheral mesopositions of the tetrapyrrole macrocycle which may largely aVect the kinetics and extent of binding to microbial cells [8]. Cationic meso-substituted porphyrins are known to eYciently destroy Gram-negative and Gram-positive bacteria [9][10][11][12][13][14]. The combination of hydrophobic and hydrophilic substituents in the PS structure results in an intramolecular polarity axis, which can facilitate membrane penetration and produce a better accumulation in subcellular compartments, enhancing the eVective photosensitization [15].…”
Section: Introductionmentioning
confidence: 99%
“…As E. coli is an indicator of faecal pollution and is used to evaluate the quality of drinking, recreational and residual waters, it can be considered an adequate bacterium model to test the applicability of the bioluminescent method. Moreover, E. coli is a Gram-negative bacterium and it is much more resistant to photoinactivation than Gram-positive bacteria [9,11,43] and consequently when E. coli cells are inactivated, it is likely that other vegetative cells of Gram-positive bacteria are also inactivated [14,44].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach for killing bacteria present in topical wounds is by lethal photosensitization, that is, the use of photodynamic therapy (PDT), which was suggested some years ago [29][30][31]. In PDT, ROS generated by an illuminated photosensitizer introduced exogenously into the bacteria induce a toxic effect [32][33][34].…”
Section: Discussionmentioning
confidence: 99%